Karakterisasi Metabolit Teh dan Tanah dari Berbagai Sumber di India Timur Laut: Characterization of Tea Metabolites and Soil of Different Origins in North Eastern India - Sudeshna Shyam Choudhury; Debapriya Maitra; Bedaprana Roy; Sejuti Ray; Sony Choubey; Bishista DasGupta; Suman Deb; Ankur Chattopadyay; Biswanath Ganguly; Arup Kumar Mitra (Jurnal Penelitian Teh dan Kina, 2026)
Tea harvested in North-Eastern parts of India is renowned for high quality tea including various therapeutic potentials like antioxidant and antimicrobial properties. Tea samples collected from Darjeeling, Assam and Jalpaiguri gardens are subjected for metabolite quality analysis processes. The geographic factors including soil characters can influence the qualities of tea according to their inherent secondary metabolites. One of the major class of tea secondary metabolite is tea flavonoids responsible for tea quality parameters including Rutin, Quercetin, Epigallocatechin gallate, Tannic acid, Gallic acid etc. Spectrophotometric, Spectrofluormetric scan analysis, HPLC, FTIR analysis characterize the differential contents of different tea flavonoids of different origin. The results suggest that tea extracts from Assam, Darjeeling, and Jalpaiguri possess valuable bioactive secondary metabolites to impart antimicrobial and antioxidant activities. The variations in these properties can be attributed to a combination of factors, including soil characteristics and cultivation practices of the different origin of North eastern Indian tea gardens